2015
DOI: 10.1194/jlr.m057612
|View full text |Cite
|
Sign up to set email alerts
|

Micellar lipid composition affects micelle interaction with class B scavenger receptor extracellular loops

Abstract: International audienceScavenger receptors (SRs) like cluster determinant 36 (CD36) and SR class B type I (SR-BI) play a debated role in lipid transport across the intestinal brush border membrane. We used surface plasmon resonance to analyze real-time interactions between the extracellular protein loops and various ligands ranging from single lipid molecules to mixed micelles. Micelles mimicking physiological structures were necessary for optimal binding to both the extracellular loop of CD36 (lCD36) and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…We observed that the presence of tocopherol in structures mimicking mixed micelles (i.e., containing a biliary salt and at least oleic acid) was necessary for transporter-dependent absorption in Caco-2 cells [ 32 ]. This is in agreement with another study in which we showed that both SR-BI and CD36 extracellular loops were able to bind postprandial mixed micelles in a more efficient manner than interprandial micelles [ 52 ]. However, this does not indicate whether this interaction is the first step of either a sensing or an absorptive process—or if the two phenomena are coexisting.…”
Section: Vitamin E Absorption Mechanisms By the Enterocytesupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that the presence of tocopherol in structures mimicking mixed micelles (i.e., containing a biliary salt and at least oleic acid) was necessary for transporter-dependent absorption in Caco-2 cells [ 32 ]. This is in agreement with another study in which we showed that both SR-BI and CD36 extracellular loops were able to bind postprandial mixed micelles in a more efficient manner than interprandial micelles [ 52 ]. However, this does not indicate whether this interaction is the first step of either a sensing or an absorptive process—or if the two phenomena are coexisting.…”
Section: Vitamin E Absorption Mechanisms By the Enterocytesupporting
confidence: 93%
“…Authors suggested that vitamin E was associated with phospholipids, leading to a low uptake. As we showed that the presence of phosphatidylcholine in mixed micelles was associated with a decreased binding of mixed micelles on scavenger receptor extracellular loops [ 52 ], we suggest that neutral phospholipids can also impact vitamin E absorption by modifying micellar interaction with the membrane proteins responsible for its uptake.…”
Section: Vitamin E Absorption Mechanisms By the Enterocytementioning
confidence: 97%
“…Mixed micelles were formed as previously described [ 16 , 17 ]. Briefly, monoolein (0.3 mM), oleic acid (0.5 mM), phosphatidylcholine (0.04 mM), lysophosphatidylcholine (0.16 mM), and cholesterol (0.1 mM) dissolved in trichloromethane/methanol (2:1, v / v ) and vitamin D forms (concentration range: 0–20 µM) dissolved in ethanol were transferred to a glass tube, and the solvent mixture was carefully evaporated under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…SR-BI was primarily shown to selectively mediate the uptake of α-tocopherol from high density lipoproteins (HDL) (12), which suggests a direct interaction with this ligand. However, SR-BI has also been shown to traffic in clathrin-coated lipid vesicles after a lipid load (18), and we demonstrated that SR-BI extracellular loop could bind mixed micelles (19). Finally, SR-BI has recently been described as an intestinal lipid sensor (20), and it appeared to be a modulator of chylomicron secretion (21).…”
Section: Introductionmentioning
confidence: 64%
“…We later showed that besides its ability to transport carotenoids (22) and possibly vitamin D (23) and K (24), intestinal CD36 (CD36 molecule) could contribute to tocopherol absorption process (25). However, despite the fact that the extracellular loop of this protein could bind mixed micelles (19) and that CD36 was clearly involved in vitamin E uptake in vitro, its effect on vitamin E absorption in vivo in mice was rather due to its impact on lipid general absorption process. Conversely to what was expected, CD36-deficient mice showed an accumulation of plasma vitamin E during the postprandial state, due to a defect of clearance of the produced chylomicrons (25).…”
Section: Introductionmentioning
confidence: 99%